The Importance of the Monitoring of Resuscitation with Blood Transfusion for Uterine Inversion in Obstetrical Hemorrhage - Seishi Furukawa; Hiroshi Sameshima (Hindawi Limited, 2015)
Objective. The aim of this study was to describe critical care for obstetrical hemorrhage, especially in cases of uterine inversion. Study Design. We extracted data for six patients diagnosed with uterine inversion concerning resuscitation. Results. The shock index on admission of the six patients was 1.6 or more on admission. Four of the six experienced delay in diagnosis and received inadequate fluid replacement. Five of the six experienced delay in transfer. Five of the six underwent simultaneous blood transfusion on admission, and the remaining patient experienced a delay of 30 minutes. All six patients successfully underwent uterine replacement soon after admission. One maternal death occurred due to inappropriate practices that included delay in diagnosis, delay in transfer, inadequate fluid replacement, and delayed transfusion. Two patients experiencing inappropriate practices involving delay in diagnosis, delay in transfer, and inadequate fluid replacement survived. Conclusion. If a delay in diagnosis occurs simultaneously with a delay in transfer and inadequate fluid replacement, failure in providing a prompt blood transfusion may be critical and result in maternal death. The monitoring of resuscitation with blood transfusion for uterine inversion is essential for the improvement of obstetrical care.